Thermal Liability of Hyaloclastite in the Krafla Geothermal Reservoir, Iceland: The Impact of Phyllosilicates on Permeability and Rock Strength. (14th July 2020) - Weaver, Josh; Eggertsson, Guðjón H.; Utley, James E. P.; Wallace, Paul A.; Lamur, Anthony; Kendrick, Jackie E.; Tuffen, Hugh; Markússon, Sigurður H.; Lavallée, Yan
Abstract : Geothermal fields are prone to temperature fluctuations from natural hydrothermal activity, anthropogenic drilling practices, and magmatic intrusions. These fluctuations may elicit a response from the rocks in terms of their mineralogical, physical (i.e., porosity and permeability), and mechanical properties. Hyaloclastites are a highly variable volcaniclastic rock predominantly formed of glass clasts that are produced during nonexplosive quench-induced fragmentation, in both subaqueous and subglacial eruptive environments. They are common in high-latitude geothermal fields as both weak, highly permeable reservoir rocks and compacted impermeable cap rocks. Basaltic glass is altered through interactions with external water into a clay-dominated matrix, termed palagonite, which acts to cement the bulk rock. The abundant, hydrous phyllosilicate minerals within the palagonite can dehydrate at elevated temperatures, potentially resulting in thermal liability of the bulk rock. Using surficial samples collected from Krafla, northeast Iceland, and a range of petrographic, mineralogical, and mechanical analyses, we find that smectite dehydration occurs at temperatures commonly experienced within geothermal fields. Dehydration events at 130, 185, and 600°C result in progressive mass loss and contraction. This evolution results in a positive correlation between treatment temperature, porosity gain, and permeability increase. Gas permeability measured at 1 MPa confining pressure shows a 3-fold increase following thermal treatment at 600°C. Furthermore, strength measurements show that brittle failure is dependent on porosity and therefore the degree of thermal treatment. Following thermal treatment at 600°C, the indirect tensile strength, uniaxial compressive strength, and triaxial compressive strength (at 5 MPa confining pressure) decrease by up to 68% (1.1 MPa), 63% (7.3 MPa), and 25% (7.9 MPa), respectively. These results are compared with hyaloclastite taken from several depths within the Krafla reservoir, through which the palagonite transitions from smectite- to chlorite-dominated. We discuss how temperature-induced changes to the geomechanical properties of hyaloclastite may impact fluid flow in hydrothermal reservoirs and consider the potential implications for hyaloclastite-hosted intrusions. Ultimately, we show that phyllosilicate-bearing rocks are susceptible to temperature fluctuations in geothermal fields.